황화물계 전해질 기반 전고체전지 연구개발 동향 - 신채연; 김수빈; 이지은 (The Korean Ceramic Society, 2025)
All-solid-state batteries (ASSBs) are emerging as the next-generation secondary battery technology to overcome the safety and energy-density limitations of conventional liquid electrolyte-based lithium-ion batteries. Sulfide-based solid electrolytes, in particular, stand out as the most promising candidate to commercialization thanks to their excellent processability and high ionic conductivity. However, their practical employment has been delayed by chemical and electrochemical instability and vulnerability to moisture. To overcome these hurdles, intensive research is underway on developing novel electrolyte structure and composition, while also pursuing low-cost, high efficiency synthesis methods. On the electrode side, efforts focus on scalable, sheet‐type electrodes fabrication by comparing wet, dry, and thermocompression processing, alongside strategies to integrate the high voltage oxide active materials, sulfur cathode, silicone anode and anode-free designs, all supported by mechanically robust ultra-thin solid electrolyte membranes. In cell assembly and cycling, simplified alternatives to warm isostatic pressing and high external stack pressures for densification are under development. By overcoming key challenges to boost energy density, cycle life, and safety, ASSBs are expected to become the leading energy storage solution for electric vehicles, air mobility, energy storage systems, and a broad range of future applications.